Detection of spotted fever group rickettsiae and Coxiella burnetii in long-tailed ground squirrels (Spermophilus undulatus) and their ectoparasites - Han, Xiaoshuang; Liu, Ziheng; Jiang, Zhixian; Zhao, Shanshan; Hornok, Sándor; Yang, Meihua; Liu, Gang; Wang, Yuanzhi (Frontiers in Veterinary Science, 2025)
Long-tailed ground squirrels (LTGRs, Spermophilus undulatus) are known as reservoirs of multiple arthropod-borne pathogens, such as Yersinia pestis and Bartonella rochalimae. However, data on the prevalence of spotted fever group rickettsiae (SFGR) and Coxiella burnetii in LTGRs and its ectoparasites are limited. In two alpine regions of Xinjiang Uygur Autonomous Region (XUAR, northwestern China), a total of 346 samples were collected from 142 LTGRs, including 142 livers and 204 pooled ectoparasites (Citellophilus tesquorum dzetysuensis: 120 pools of 484 fleas; Frontopsylla elatoides elatoides: 19 pools of 71 fleas; Neopsylla mana: 1 pool of 4 fleas; and Linognathoides urocitelli: 64 pools of 865 lice). From these samples, the DNA was extracted, followed by PCR amplification of different genetic markers. Particularly, genes encoding the outer membrane protein A and B (ompA, ompB), citrate synthase (gltA), and surface cell antigen 1 (sca1) were used to identify the SFGR. Additionly, the capsular outer membrane protein (Com1) gene and insertion sequence (IS1111) genes were used to detect Coxiella. Rickettsia sibirica subsp. sibirica, Rickettsia felis, and C. burnetii were detected in LTGRs, as well as in flea and louse pools. Rickettsia raoultii was found in LTGRs and flea pools. Furthermore, Rickettsia slovaca was also identified in the flea pools. This study provides molecular evidence for the occurrence of SFGR and C. burnetii in LTGRs and their ectoparasites. These findings suggest that R. sibirica, R. slovaca, R. raoultii, R. felis and C. burnetii are transmitted between LTGRs (as potential reservoirs) and their fleas and lice (as potential vectors).